2022
DOI: 10.1186/s40538-022-00357-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites, elemental profile and chemical activities of Pinus strobus high temperature-derived pyroligneous acid

Abstract: Background Pyroligneous acid (PA) is an aqueous smoky fraction produced during pyrolysis of biomass. The chemical composition of PA from different plant biomass has been studied, but reports on PA metabolites and elemental profiles are rare. In this study, we examined the metabolites, elemental profiles and the associated chemical activities of PA derived from white pine (Pinus strobus) at 1100 °C compared to similar work done elsewhere using different biomass at lower temperatures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…This result is consistent with previous studies where a similar increase in chlorophyll content with different PA concentrations have been reported 12,15,17,18,39 . Besides, the PA used in this study was previously revealed to contain high levels of N, K and Ca as well as other bioactive compounds 10 . In plants, N is a key modulator of nitrogenous compounds biosynthesis including chlorophyll and proteins, K is critical in enzyme activation, stomatal regulation and photosynthesis while Ca facilitate nutrient uptake and cell elongation 44,45 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This result is consistent with previous studies where a similar increase in chlorophyll content with different PA concentrations have been reported 12,15,17,18,39 . Besides, the PA used in this study was previously revealed to contain high levels of N, K and Ca as well as other bioactive compounds 10 . In plants, N is a key modulator of nitrogenous compounds biosynthesis including chlorophyll and proteins, K is critical in enzyme activation, stomatal regulation and photosynthesis while Ca facilitate nutrient uptake and cell elongation 44,45 .…”
Section: Discussionmentioning
confidence: 91%
“…The increase in DPPH activity was highly expected and may be correlated with enhanced phytochemical content as previously reported 16,23 . Additionally, it was reported that the high phenolic content of PA exhibited high anti-lipid peroxidation and antioxidant capacity 10,11,33 . These ndings suggest that foliar PA application with NPK fertilizer combination may be considered as an environmentally friendly plant growth promotion technique to increase fruit nutritional quality and promote health bene ts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations